Intensitas Dan Sosialitas Keberagaman Di Lingungan/Unit Kerja - Yusuf Siswantara; Thomas Lingga; Willfridus Demetrius Siga (JURNAL SOSIAL HUMANIORA (JSH), 2021)
Research "intensity and sociality of diversity in the environment or work unit", aims to find indications of work effectiveness and the values of diversity in a pluralistic work environment on work optimization and productivity. This study uses a quantitative approach with a questionnaire as a random sampling instrument. The data population is 39 respondents. The correlation of the intensity of diversity values and work practices in a pluralistic environment is the main aspect that supports work effectively both internally and externally. Positive influence supports each person to feel safe, comfortable, and have very good relationships. Based on the results of the analysis, this study shows that there is a strong and positive correlation between performance and tolerance values in a pluralistic environment with a positive percentage of 93% and 0.7% value deviation that does not support the correlation of the two variables